2022
DOI: 10.1186/s13731-022-00211-w
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing financial performance of the banks: the role of customer response and operations management

Abstract: The current study investigates the relations between the following variables customer response, operations management, and financial performance. The questionnaires were distributed among the board of upper management, middle management, and first-line management in Al-Tadamon Islamic bank in Sudan. Then, the feedbacks were analyzed using SPSS, and the response rate was 77%. The outcomes displayed that, the customer response effect positively operations management and financial performance. Similarly, operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…The CAMELS approach, which stands for Capital adequacy, Asset quality, Management capabilities, Earnings sufficiency, Liquidity position, and Sensitivity to market risk, is a widely used method for analyzing a bank's performance. Additionally, factors such as customer response, operations management, and market share are also considered in evaluating a bank's financial performance (Enad et al, 2022).…”
Section: Bank Financial Performance Analysismentioning
confidence: 99%
“…The CAMELS approach, which stands for Capital adequacy, Asset quality, Management capabilities, Earnings sufficiency, Liquidity position, and Sensitivity to market risk, is a widely used method for analyzing a bank's performance. Additionally, factors such as customer response, operations management, and market share are also considered in evaluating a bank's financial performance (Enad et al, 2022).…”
Section: Bank Financial Performance Analysismentioning
confidence: 99%
“…The concept of financial performance is multifaceted and can be influenced by a variety of factors, including the size of the organization, industry, and geographic location (Lar Lindbergh, 2003). Improving financial performance is a key goal for many organizations, it is closely related to customer response and operations management (Enad & Gerinda, 2022). Studies on companies' financial performance during the COVID-19 pandemic found that the impact of subjective and objective financial knowledge and economic insecurity on financial management behavior is mediated by financial well-being.…”
Section: Financial Performancementioning
confidence: 99%
“…This is influenced by a variety of factors, including customer response, operations management, and the broader economic context. By understanding these factors and how they affect financial performance, organizations can develop strategies to improve financial performance and achieve goals (Enad & Gerinda, 2022) (Lam et al, 2023).…”
Section: Financial Performancementioning
confidence: 99%
“…The word “Performance” has been derived from the term “performed” which means “to do,” “to carry out” or “to render” (Enad and Gerinda, 2022). However, defining, conceptualizing and measuring performance has not been an easy task.…”
Section: Introductionmentioning
confidence: 99%